2015
DOI: 10.1590/s1808-185120151402145324
|View full text |Cite
|
Sign up to set email alerts
|

Iphone app use to Cobb angle in adolescent idiopathic scoliosis: Does this apply?

Abstract: <sec><title>OBJECTIVE:</title><p> To validate a new method of measuring the Cobb angle for scoliosis from the mobile app CobbMeter to facilitate the evaluation and measurement in clinical practice.</p></sec><sec><title>METHODS:</title><p> Five observers with minimum experience of two years in the field performed radiographic measurements of Cobb angle in 24 radiographs of patients with adolescent idiopathic scoliosis through the CobbMeter. Observers p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 5 publications
0
6
0
1
Order By: Relevance
“…Therefore, the use of the cellular application insures measurements that are comparable and correlated to those acquired using the traditional measurement acquisition method proposed by Cobb. 23 Other studies have already studied the use of smartphone applications to measure vertebral parameters, whether coronal 24,25 (Cobb angles in scoliosis) or sagittal 15 (kyphosis). Unlike earlier studies, this work measured spino-pelvic sagittal angles, which involve not only vertebral plateau lines, but also imaginary lines drawn between two anatomical points (such as for example the line that joins the center of the femur heads and the center of the S1 plateau).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the use of the cellular application insures measurements that are comparable and correlated to those acquired using the traditional measurement acquisition method proposed by Cobb. 23 Other studies have already studied the use of smartphone applications to measure vertebral parameters, whether coronal 24,25 (Cobb angles in scoliosis) or sagittal 15 (kyphosis). Unlike earlier studies, this work measured spino-pelvic sagittal angles, which involve not only vertebral plateau lines, but also imaginary lines drawn between two anatomical points (such as for example the line that joins the center of the femur heads and the center of the S1 plateau).…”
Section: Discussionmentioning
confidence: 99%
“…[66] Scoliosis [67] Rib Hump Angle/Scoliosis [68] Kyphotic Angles [69] Cobb Angle/Thoracic Scoliosis [70] Cobb Angle/Thoracic Scoliosis [71] Lumbar Lordosis [72] Rib Hump Angle/Scoliosis Evaluation [73] Cobb Angle of Thoracolumbar Scoliosis [74] Cobb Angle [75] Cobb Angle [76] Cobb Angle [77] Head, Ribcage, Shoulder, Hip and Knee Tilt [65] Inclination of the Human Spinal Points [78] SS and Lumbar Curve [79] PI, PT and LL [80] Sagittal Curvaures [81] Thoracic Spine Rotation [82] LL, PI, and PT [83] Head, Ribcage, Shoulder, Hip Tilt [84] Head, Ribcage, Shoulder, Hip Inclination [85] Scoliosis Angle [86] Head, Shoulder and Ribcage Tilt [87] Head, Ribcage, Shoulder, Hip and Knee Tilt [88] LL, PI, SS and PT [89] LL, PT, and SS [90] Rib Hump/Scoliosis Evaluation Note: LL = Lumbar Lordosis; PI = Pelvic Incidence; SS = Sacral Slope; PT = Pelvic Tilt.…”
Section: Study Measures Takenmentioning
confidence: 99%
“…Regarding the US applications, although they have used sensors embedded in smartphones (i.e., accelerometer and gyroscope), they varied in relation to the measurement methods used by the assessors. Some studies [68][69][70][74][75][76]79,82,92] used applications to analyze radiographs of the spine. For example, the method proposed by Allam et al [76] positioned radiographs in the vertical plane on a backlit X-ray reader box.…”
Section: Study Measures Takenmentioning
confidence: 99%
“…The review of Moreira et al investigated the studies regarding posture assessment tools between the year 2012 and 2020, and they reported 13 mobile apps for assessing posture [12]. A majority of these apps were developed specifically for analysis of spinal orientation such as lordosis, kyphosis, scoliosis postures, and Cobb angle [18][19][20]. Furthermore, 11 of 13 apps were classified as sensor-based (accelerometer or gyroscope) apps that have diverse approaches such as using assessment of radiographs [21] or direct contact with the body of patients [12,22].…”
Section: Introductionmentioning
confidence: 99%